2014
DOI: 10.1097/sle.0b013e3182937980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Standard-pressure and Low-pressure Pneumoperitoneum in Laparoscopic Cholecystectomy

Abstract: The use of low-pressure pneumoperitoneum (8 mm Hg) for LC is associated with a significantly lower postoperative pain. However, the use of this low-pressure pneumoperitoneum can jeopardize the surgeon's comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 13 publications
(17 reference statements)
1
38
0
2
Order By: Relevance
“…For example, the beneficial effects of low-pressure procedures on liver function were demonstrated in some studies (13)(14)(15). However, some studies showed the side effects of low-pressure and standardpressure pneumoperitoneum in laparoscopic cholecystectomy on different organs are comparable (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the beneficial effects of low-pressure procedures on liver function were demonstrated in some studies (13)(14)(15). However, some studies showed the side effects of low-pressure and standardpressure pneumoperitoneum in laparoscopic cholecystectomy on different organs are comparable (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative respiratory complications prolong the length of hospital stay of patients, with a consequent increase in hospital costs and significantly contributing to patient mortality 26 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Various authors have reported that laparoscopic cholecystectomy performed with LPP results in a better postoperative quality of life as compared to laparoscopic cholecystectomy performed with HPP. [16][17][18] In our study contact of parietal peritoneum to the underlying viscera during secondary port insertion under vision after insertion of primary port, was taken as indirect indicator of potential of causing visceral injury at a particular intraabdominal pressure. Out of 180 secondary ports inserted, there was evident contact of 20 (11.1%) secondary ports in high pressure groups and 14 (7.7%) secondary ports in low pressure group, which is suggestive of adequate exposure and working space available for surgery at both pressures.…”
Section: Discussionmentioning
confidence: 99%